2020
DOI: 10.1002/pros.23974
|View full text |Cite
|
Sign up to set email alerts
|

Influence of short‐term dexamethasone on the efficacy of 177Lu‐PSMA‐617 in patients with metastatic castration‐resistant prostate cancer

Abstract: Background and Aim: Corticosteroids alone or in combination therapy are associated with favorable biochemical responses in metastatic castration-resistant prostate cancer (mCRPC). We speculated that the intermittent addition of dexamethasone may also enhance the antitumor effect of radioligand therapy (RLT) with 177 Lu-prostate-specific membrane antigen (PSMA)-617.Patients and Methods: Seventy-one patients with mCRPC were treated with 1 to 5 cycles of 177 Lu-PSMA-617 (6.0-7.4 GBq per cycle) at 6 to 8 weeks int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 30 publications
(46 reference statements)
1
21
2
Order By: Relevance
“…Gafita et al [37] found no association between PSA level and either PFS or OS, in a cohort with the median PSA baseline of 126 ng/ml (IQR: 37-368). Moreover, Derlin et al [38] found no [39] or any PSA response [40]. In summary, the prognostic value of baseline PSA level has been controversially discussed, which warrants further investigations.…”
Section: Predictive Factorsmentioning
confidence: 96%
See 4 more Smart Citations
“…Gafita et al [37] found no association between PSA level and either PFS or OS, in a cohort with the median PSA baseline of 126 ng/ml (IQR: 37-368). Moreover, Derlin et al [38] found no [39] or any PSA response [40]. In summary, the prognostic value of baseline PSA level has been controversially discussed, which warrants further investigations.…”
Section: Predictive Factorsmentioning
confidence: 96%
“…Also, the same research group reported that a baseline LDH level of < 248 mg/L and any change after the first cycle could predict better survival [32]. However, others did not find a correlation between higher LDH and response to therapy or OS [24,38,39,63]. Moreover, some authors showed that abnormal pre-treatment LDH has no prognostic value for predicting OS [23,33,36].…”
Section: Lactate Dehydrogenasementioning
confidence: 99%
See 3 more Smart Citations